1993
DOI: 10.1037/1040-3590.5.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Wiener-Harmon Subtle-Obvious scales and the standard validity scales in detecting valid and invalid MMPI-2 profiles.

Abstract: The results from this study were presented in part at the 26th Annual Symposium on Recent Developments in the Use of the MMPI, St. Petersburg Beach, FL.The authors wish to thank Yossef S. Ben-Porath for his many helpful comments and suggestions made on earlier versions of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
38
4

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 19 publications
10
38
4
Order By: Relevance
“…Since response style should be considered (Bannatyne et al, 1999;, and distortion should be assumed in all forensic evaluations (Meloy, 1989), the MMPI-2 validity scales take on special importance when assessing psychopathy. It appears that Scales L and F remain the most useful in classifying fake-bad and fake-good profiles (Timbrook, Graham, Keillor, & Watts, 1993), but attention must be paid to the relative configurations of VRIN, TRIN, Fb, Ds, and F(p). Megargee (2006b) has also developed a criminal infrequency scale (Fc) which may prove to be helpful in identifying problematic profiles among criminal offenders.…”
Section: The Mmpi-2mentioning
confidence: 99%
“…Since response style should be considered (Bannatyne et al, 1999;, and distortion should be assumed in all forensic evaluations (Meloy, 1989), the MMPI-2 validity scales take on special importance when assessing psychopathy. It appears that Scales L and F remain the most useful in classifying fake-bad and fake-good profiles (Timbrook, Graham, Keillor, & Watts, 1993), but attention must be paid to the relative configurations of VRIN, TRIN, Fb, Ds, and F(p). Megargee (2006b) has also developed a criminal infrequency scale (Fc) which may prove to be helpful in identifying problematic profiles among criminal offenders.…”
Section: The Mmpi-2mentioning
confidence: 99%
“…The Infrequency scale ( F ; Greene, I99 l), Obvious and Subtle subscales (04; Wiener, 1948;Timbrook, Graham, Keiller, & Watts, 1993) and the Dissimulation Index (F-K, Gough, 1950) were developed as means of detecting exaggeration or outright manufacture of complaints atypical of psychiatric syndromes. The L scale was developed to detect extreme defensiveness, that is, the active attempt to hide or deny adjustment problems.…”
mentioning
confidence: 99%
“…The clinical use of the Wiener and Harmon (Wiener, 1948) Subtle and Obvious scales has had a long and controversial history. Originally developed to detect deviant test-taking attitudes in the MMPI, the clinical utility of the Subtle and Obvious scales is questionable, as research that used the original MMPI clearly has shown (Dannenbaum & Lanyon, 1993;Herkov, Archer, & Gordon, 1991;Peterson, Clark, & Bennett, 1989;Rogers, 1983;Schretlen, 1988Schretlen, , 1990Wrobel & Lachar, 1982) and MMPI-2 (Berry, Baer, & Harris, 1991;Boone, 1994a;Butcher, 1989;Graham, Watts, & Timbrook, 1991;Herkov, Gordon, Gynther, & Greer, 1994;Peterson et al, 1989;Timbrook, Graham, & Watts, 1993;Weed, Ben-Porath, & Butcher, 1990). To summarize, the Subtle and Obvious scales "have led to ambiguous identification of faking" (Dubinsky, Gamble, & Rogers, 1985, p. 67) and may "attenuate the validity of the Full Scale by introducing variance that is not related to variance in the criterion measure" (Weed et al, 1990, p. 12).…”
mentioning
confidence: 99%